Fiscal Policy Announcements of Italian Governments and Spread Reaction during the Sovereign Debt Crisis - Matteo Falagiarda; Wildmer Daniel Gregori (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2014)
This paper attempts to evaluate the effects of fiscal policy announcements by the Italian government on the long-term sovereign bond spread of Italy relative to Germany. After collecting data on relevant fiscal policy announcements, we perform an econometric comparative analysis between the three cabinets that followed one another during the period 2009-2013. The results suggest that only fiscal policy announcements made by members of Monti's cabinet have been effective in influencing the Italian spread, revealing a remarkable credibility gap between Monti's technocratic administration and Berlusconi's and Letta's governments.
Keywords: E43; E62; G01; G12; 330